Konsep Emanasi Filsuf Islam dan Hubungannya dengan Teori Sains mengenai Penciptaan Alam Semesta - Yusuf, Muhammad; al-Rasyid, Hamzah Harun; Latif, Muhaemin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Discussions about the universe are still debated today. Over the next few generations, these ideas received many responses, both pros and cons related to the concept of emanation. This article aims to examine several views of Islamic philosophers regarding the concept of emanation which is connected to the concept of the creation of the universe based on modern science. This research is included in the library research category, namely research that uses documents and literature data to help find a synthesis of the data being analyzed. Based on this study, it appears that the concept of emanation developed by Al-Farabi and Ibn Sina is in accordance with the Big Bang theory or Big Bang. However, the concept of emanation between the two still results in disagreement with the concept of creation held by the beliefs of Muslims in general.